Enhancing Productivity in Agricultural Packing Operations through TPM and Lean Manufacturing: A Case Study of Asparagus Processing in Peru - Farah Alva, Macarena Thais (2024)
This study investigates the integration of Total Productive Maintenance (TPM) and Lean methodologies within the Peruvian agricultural sector, focusing on asparagus packing operations. A model was developed to address critical challenges of low productivity, employing autonomous and preventive maintenance strategies to reduce unplanned downtime and the implementation of Standardized Work to eliminate inefficiencies. A pilot project was implemented using a sample of 72.98 kg of processed asparagus, using processing times from each activity as input data for the model’s validation. The Kolmogorov-Smirnov and Chi-square statistical tests were applied to establish time distributions. The proposed model, validated through Arena software, demonstrated a 21% increase in packing productivity, a 36 kg/man-hour improvement in labor productivity, and a 26.35% enhancement in machinery availability. These findings provide a replicable framework for medium-sized agro-exporting companies, enhancing their operational efficiency and competitiveness within global markets. The research contributes to the limited literature on Lean and TPM applications in agricultural processes, highlighting their potential to bridge productivity gaps in developing countries.